Relações interorganizacionais e a percepção de valor em serviços de contact center - Notarnicola Filho, Onófrio (2019)
The Contact Center, is the environment where this research was developed, is a place where it integrates advanced technology with an effective design in the business processes, and human resources. Since the 1980s, customer service has been disseminated through the advancement of technology companies and telematic products. Initially the service area was part of the company, and then, business configurations started to adopt this service by a hybrid governance model, depending on the level of service expected. Technologies allow service activities to be allocated anywhere; is a geographically mobile industry. The governance models based on outsourcing or partnership evidenced interorganizational relationships as a means of generating value to the participants of the agreement. From the perspective of Resource-Based Vision and Relational View, the interactions established with service providers can become a source of competitiveness. Since the ability to relate can be developed through well-defined management structures, service delivery criteria, skills that promote information exchange, joint problem solving, limited use of power, and other characteristics, one can considered as an intangible resource, valuable for the quality of services, and not easily identified and imitated. For this, we chose to conduct an exploratory-descriptive research, of a qualitative nature, with four distinct companies in the Contact Center sector and the applied technologies: two companies contracted for contact center services, and two contracting companies of these contracting services. The empirical step was organized to capture perceived value in the relationship between companies - Business to Business B2B - companies contracted for services and contracting companies, through semi-structured interviews using two different routes, one for contractors and the second for contractors of services. Finally, the research provided a theoretical contribution to the concept and construct of relational and practical capacity on the characteristics of the potential organizational relational capacity that generates value to clients.